Intelligent reprogramming of wheat for enhancement of fungal and nematode disease resistance using advanced molecular techniques - Jabran, Muhammad; Ali, Muhammad Amjad; Zahoor, Adil; Muhae-Ud-Din, Ghulam; Liu, Taiguo; Chen, Wanquan; Gao, Li (Frontiers in Plant Science, 2023)
Wheat (Triticum aestivum L.) diseases are major factors responsible for the substantial yield losses worldwide, which affect global food security. Since long, plant breeders have been struggling to improve wheat resistance against major diseases by selection and conventional breeding techniques. Therefore, this review was conducted to shed light on various gaps in the available literature and to reveal the most promising criteria for disease resistance in wheat. However, novel techniques for molecular breeding in the past few decades have been very fruitful for developing broad-spectrum disease resistance and other important traits in wheat. Many types of molecular markers such as SCAR, RAPD, SSR, SSLP, RFLP SNP, and DArT etc. have been reported for resistance against wheat pathogens. This article summarizes various insight molecular markers involved in wheat improvement for resistance to major diseases through diverse breeding programs. Moreover, this review highlights the applications of marker assisted selection (MAS), Quantitative trait locus (QTL), Genome wide association studies (GWAS) and CRISPR/Cas-9 system for developing disease resistance against most important wheat diseases. We also reviewed all reported resistant genes and mapped QTLs for bunts, rusts, smuts, and nematode diseases of wheat. Furthermore, we have also proposed how CRISPR/Cas-9 system and GWAS can assist breeders in future for the genetic improvement of wheat. If these molecular approaches are used successfully in future, it can be a significant step toward expanding food production in wheat crop.